2014
DOI: 10.1684/ejd.2013.2216
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic skin lesions of the scalp in children: A retrospective study of 265 cases in Taiwan

Abstract: Background: The preferential occurrence of certain skin neoplasms on the scalp of children raises concerns from their parents and warrants special diagnostic and therapeutic approaches. Objective: To explore the demographic and clinical characteristics of scalp neoplasms in the pediatric population, with attention to malignant tumors and systemic syndromes. Methods: Scalp neoplasms in patients aged 12 years or younger were retrospectively collected in 1990-2010 from two tertiary referral centers in Taiwan. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…The comparison among similar series is summarized in Table III. A few reports consisted only of malignant tumors of the scalp (6-10) and one was performed on a pediatric population (11). In our study, we found that the majority of malignant scalp tumors occurred in middle-aged and elderly individuals, which is consistent with the previous reports (6-10).…”
Section: Discussionsupporting
confidence: 92%
“…The comparison among similar series is summarized in Table III. A few reports consisted only of malignant tumors of the scalp (6-10) and one was performed on a pediatric population (11). In our study, we found that the majority of malignant scalp tumors occurred in middle-aged and elderly individuals, which is consistent with the previous reports (6-10).…”
Section: Discussionsupporting
confidence: 92%
“…265,271 There is a diffuse and dense dermal infiltrate with extension into the subcutaneous tissue ( Figure 14). 4,234,263,264,[268][269][270]272 A Grenz zone is typically present with epidermal sparing. Cytologically, the infiltrate consists of small lymphoblasts with scant cytoplasm, fine nuclear chromatin, irregular nuclei, and inconspicuous nucleoli.…”
Section: Precursor T/b-cell Lymphoblastic Leukemias/ Lymphomasmentioning
confidence: 99%
“…Some cases of JXG follow the diagnosis of LCH. 272,[396][397][398][399][400][401][402] More recently, systemic presentations of JXG with CNS involvement have shown BRAF V600E mutations. 386,387 The question that arises from these is: Should those cases be qualified as ECD/L group lesions that have not presented themselves with systemic findings (ie, brain only), or is there a truly separate group of JXG/BRAF V600E positive tumors?…”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…This meta-analysis produced an incidence of secondary malignancy lower than studies published before 2000 (with reported rates of development of BCC up to 14% 25,27 ), being more consistent with recent publications. 4,11,38,42,44 Several reasons for this discrepancy exist. First, earlier studies may have misdiagnosed basaloid proliferations as BCC.…”
Section: Malignant Lesionsmentioning
confidence: 99%